"Our tears are not enough": The warrant of the dead in the rhetoric of gun control. Issue 1 (2nd January 2018) - Rood, Craig
ABSTRACT: The warrant of the dead refers to an explicit or implicit claim that the dead place a demand on the living. The living are called on to act and the dead are invoked as justification for that action: since they died, we should do X. Seeing this rhetorical move as a warrant is useful because the connection between the dead and the requested action of the living is often assumed rather than argued outright. This essay examines how, why, and to what effect President Barack Obama used the warrant of the dead in his gun control rhetoric since the mass shooting at Sandy Hook Elementary School on December 14, 2012. By extending, expanding, and intensifying memories of the victims of gun violence, Obama used the warrant of the dead to try to establish sustained concern for those victims and thus sustained commitment to gun control. Yet Obama's effort to transform gun control supporters into gun control activists proved largely ineffective. Examining this partial rhetorical failure offers rhetorical scholars important insights about the warrant of the dead, the gun debate, and, more generally, the challenges of public argument and deliberation in an era of fleeting engagement.